Preventing Bullying in Integrated Islamic Boarding Schools of Lhokseumawe City: A Strategic Management Approach - Alwi, Said; Iqbal, Muhammad; Manas, Nur Hidayahtul Nabihah (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
Abstact: This study aims to analyze the role of Islamic boarding school residents in preventing bullying behaviour among students in integrated boarding schools in the city of Lhokseumawe. This research adopts a qualitative research design with a phenomenological approach. Data collection techniques are carried out through participant observation, in-depth interviews, and documentation. The research informants consist of the Islamic boarding school leaders and caregiving staff. Data validity is ensured through source verification techniques. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. Bullying behaviour in Dayah Terpadu Ulumuddin and Pesantren Misbahul Ulum Integrated Boarding Schools is prevented by the boarding schools’ authorities through measures such as reprimanding, advising, punishment, and involving parents. However, the psychological approach has not been fully implemented due to the lack of counselling teachers in the boarding school. The boarding schools’ authorities provide guidance and advice to bullying victims. Some bullying behaviours are considered normal among the students, such as teasing and using nicknames. This behaviour will receive less attention from the boarding school authorities. However, if the bullying involves physical violence, the victim will receive special attention. Abstrak: Penelitian ini bertujuan untuk menganalisis peran warga pesantren dalam pencegahan perilaku bulliying pada santri di pesantren terpadu Kota Lhokseumawe. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data dilakukan melalui observasi partisipan, wawancara mendalam, dan dokumentasi. Informan penelitian ini terdiri dari pimpinan dayah, bidang pengasuhan. Pemeriksaaan keabsahan data dilakukan dengan teknik pemeriksaan melalui sumber. Teknik analisis data dilakukan dengan cara reduksi data, penyajian data, dan penarikan kesimpulan. Perilaku bullying di Dayah Terpadu Ulumuddin dan Misbahul Ulum dicegah oleh pihak dayah terhadap pelaku bullying, yaitu memberikan teguran, nasihat, hukuman, dan pemanggilan orang tua, sedangkan pendekatan psikologis belum dilaksanakan secara maksimal karena belum tersedianya guru bimbingan konseling di dayah. Tindakan pihak dayah terhadap korban bullying berupa pembinaan dan pemberian nasihat. Perilaku bullying yang dianggap wajar terjadi, seperti mengejek dan memanggil dengan nama julukan kurang mendapat perhatian dari pihak dayah. Akan tetapi, jika bullying yang bersifat fisik seperti pemukulan, korban akan mendapat perhatian khusus.